Small Crown-Ether Complexes as Molecular Models for Dihydrogen Adsorption in Undercoordinated Extraframework Cations in Zeolites - Wulf, Toshiki; Heine, Thomas (Journal of Physical Chemistry C, 2020)
1:1 metal complexes of small crown ethers are structurally similar to extraframework sites in metal-exchanged zeolites. Using ab initio calculations, we show that adsorbed molecular hydrogen follows the same trends in adsorption energies and vibrational frequencies at both types of metal sites. Unlike zeolites, crown ethers can be characterized in the gas phase, which opens new possibilities for understanding the bonding of dihydrogen at undercoordinated metal sites to help guide the rational design of porous materials for hydrogen isotope separation. Because more strongly binding adsorbates affect the geometry of the hosts, the similarity of crown ethers and zeolites with regard to the vibrational spectra of the adsorbed molecule seems to be limited to H2
CRIS-Team Scopus Importer:2022-04-14